Analisis Elemen Brand Equity terhadap Brand Loyalty dengan Brand Trust sebagai Variabel Intervening pada Shopping Goods Laptop Merek Terpopuler di Solo Raya - Dila Aristantia Kartika Sari; Moechammad Nasir (Universitas Nusantara PGRI Kediri, 2025)
The research was conducted to analyze the effect of brand awareness, brand association, and perceived quality on brand loyalty with the intervening variable of brand trust on Asus and Acer brand laptops. The method used is a quantitative approach. The sampling technique was carried out through non-probability sampling based on purposive sampling approach. Data was collected by applying questionnaire techniques and data analysis applying Partial Least Square (PLS) by utilizing SmartPLS assistance. The results of the analysis reveal that brand awareness and perceived quality influence brand trust also brand loyalty in significant positive way on Asus also Acer brand laptops. Brand association also affects brand trust and brand loyalty significantly positively on Acer laptops, but has no effect on Asus laptops. Brand trust is also able to mediate between brand awareness, brand association, and perceived quality in influencing brand loyalty on Asus also Acer brand laptops.